Beyond mechanistic interaction: value-based constraints on meaning in language - Rączaszek-Leonardi, Joanna; Nomikou, Iris (Frontiers in Psychology, 2015)
According to situated, embodied, distributed approaches to cognition, language is a crucial means for structuring social interactions. Recent approaches that emphasize the coordinative function of language treat language as a system of replicable constraints that work both on individuals and on interactions. In this paper we argue that the integration of replicable constraints approach to language with the ecological view on values allows for a deeper insight into processes of meaning creation in interaction. Such synthesis of these frameworks draws attention to important sources of structuring interactions beyond the sheer efficiency of a collective system in its current task situation. Most importantly the workings of linguistic constraints will be shown as embedded in more general fields of values, which are realized on multiple time-scales. Since the ontogenetic timescale offers a convenient window into a process of the emergence of linguistic constraints, we present illustrations of concrete mechanisms through which values may become embodied in language use in development.